Actuation driven pseudocrease mechanics in multistable curved-crease origami shells - Kevin T. Liu; Tomohiro Tachi; Glaucio H. Paulino (Proceedings of the National Academy of Sciences, 2026)
Shells are lightweight load-bearing structures found ubiquitously throughout nature and engineering. Reconfigurable structures can change form and function, while multistable ones enable fast, large shape changes and the ability to maintain a deformed shape without the continuous input of work. Here we present a general design method for multistable shells inspired by curved-crease origami and the differential geometry of developable surfaces. Through detailed analysis of a reference multistable shell, we show that the shell naturally concentrates deformation along a band which we term a “pseudocrease.” We analyze the effect geometric parameters have on the mechanical behavior to provide an intuitive understanding of the mechanics underlying the multistability, in which bending and stretching energies within the shell compete. We validate the numerical models and trends through experiments using samples of varying geometries. The validation addresses applications across a variety of length scales and forms, including a magnetically controlled curved-crease robot capable of morphing, rolling, steering, and crawling. Our approach holds potential for designing reconfigurable shells with tailored stiffness, energy barrier, and shape across multiple application areas.